INFLUENCE OF THE TRIPLE BOTTOM LINE CONCEPT ON SUSTAINABILITY AND SUCCESS OF TOFU SMEs IN MAGELANG - Isnu Niki Adi Kurnia; Mohamad Hasanudin; Alvianita Gunawan Putri (Politeknik Negeri Semarang, 2023)
Business sustainability is essential for enterprises to endure in the future and provide economic, social, and environmental opportunities for future generations. By establishing business sustainability in economic, social, and environmental aspects, a business can enhance its success. This study seeks to analyse business sustainability and success in tofu SMEs in Magelang Regency, with a focus on sustainable practices. The study was conducted using purposive sampling technique with specific criteria and considerations to determine the sample. A total of 60 participants from the tofu industry hub in Candimulyo District were included in the sample. The analysis employed quantitative methods and a descriptive analysis approach, using variables and indicators. The research findings indicate that the sustainability of tofu SMEs is influenced by economic, social, and environmental variables within the triple bottom line concept. Meanwhile, the success of small and medium-sized enterprises producing tofu is determined by economic and social factors, operating within the framework of the triple bottom line concept.